Perforated Meckel diverticulitis: Diagnostic challenges and surgical outcomes - Imen Ben Ismail, MD; Mohamed Karim Tounsi, MD; Mohamed Boujemaa, MD; Hakim Zenaidi, MD; Saber Rebii, MD; Ayoub Zoghlami, MD (Radiology Case Reports)
Meckel's diverticulum, a congenital anomaly of the omphalomesenteric duct, is a rare cause of acute abdomen and poses significant diagnostic challenges due to its variable presentation and complications such as perforation. We present the case of a 19-year-old male with a 24-hour history of right iliac fossa pain progressing to generalized abdominal tenderness. Laboratory results showed leukocytosis and elevated C-reactive protein, while CT imaging suggested pneumoperitoneum and an inflamed Meckel diverticulum. Laparoscopic exploration, followed by conversion to laparotomy, confirmed a perforated Meckel diverticulum, which was resected with an uneventful recovery. This case highlights the importance of including Meckel's diverticulum in the differential diagnosis of acute abdomen in young patients, emphasizing the utility of CT imaging and the need for prompt surgical intervention to achieve favorable outcomes.